Distinct lipid bilayer compositions have general and protein-specific effects on K(+) channel function - Winterstein, Laura-Marie (J Gen Physiol, 2021)
It has become increasingly apparent that the lipid composition of cell membranes affects the function of transmembrane proteins such as ion channels. Here, we leverage the structural and functional diversity of small viral K(+) channels to systematically examine the impact of bilayer composition on the pore module of single K(+) channels. In vitro–synthesized channels were reconstituted into phosphatidylcholine bilayers ± cholesterol or anionic phospholipids (aPLs). Single-channel recordings revealed that a saturating concentration of 30% cholesterol had only minor and protein-specific effects on unitary conductance and gating. This indicates that channels have effective strategies for avoiding structural impacts of hydrophobic mismatches between proteins and the surrounding bilayer. In all seven channels tested, aPLs augmented the unitary conductance, suggesting that this is a general effect of negatively charged phospholipids on channel function. For one channel, we determined an effective half-maximal concentration of 15% phosphatidylserine, a value within the physiological range of aPL concentrations. The different sensitivity of two channel proteins to aPLs could be explained by the presence/absence of cationic amino acids at the interface between the lipid headgroups and the transmembrane domains. aPLs also affected gating in some channels, indicating that conductance and gating are uncoupled phenomena and that the impact of aPLs on gating is protein specific. In two channels, the latter can be explained by the altered orientation of the pore-lining transmembrane helix that prevents flipping of a phenylalanine side chain into the ion permeation pathway for long channel closings. Experiments with asymmetrical bilayers showed that this effect is leaflet specific and most effective in the inner leaflet, in which aPLs are normally present in plasma membranes. The data underscore a general positive effect of aPLs on the conductance of K(+) channels and a potential interaction of their negative headgroup with cationic amino acids in their vicinity.